Sarcopenia, Relative Sarcopenia and Excess Adiposity in Chronic Kidney Disease. Issue 1 (1st January 2018) - Ziolkowski, Susan L; Long, Jin; Baker, Joshua F; Simard, Julia F; Chertow, Glenn M; Leonard, Mary B
Abstract: Aims: Conventional definitions of sarcopenia based on lean mass fail to capture low lean mass relative to fat mass, i.e., relative sarcopenia. Unlike percent body fat (%BF) and Quételet's (body mass) index (BMI, kg/m 2 ), definitions of obesity based on fat mass index (FMI, kg/m 2 ) are not confounded by lean mass. The objective is to determine the prevalence of sarcopenia, relative sarcopenia, and obesity in CKD, and determine if CKD is associated with relative sarcopenia and obesity, independent of demographics and comorbidities. Methods and Results: DXA‐derived appendicular lean mass index (ALMI, kg/m 2 ) and FMI were assessed in 13, 980 NHANES participants. ALMI, FMI, and ALMI relative to FMI (ALMI FMI ) were expressed as sex‐ and race/ethnicity‐specific standard deviation scores compared with young adults (T‐scores) and by age (Z‐scores). Sarcopenia was defined as ALMI T‐score < −2, relative sarcopenia as ALMI FMI T‐score < −2, and low lean mass relative to fat mass for age as ALMI FMI Z‐score < −1. Obesity was defined using conventional BMI and %BF cutpoints and as sex‐ and race/ethnicity‐specific FMI cutpoints. Glomerular filtration rate (GFR) was estimated using creatinine‐ (eGFRCr ) and cystatin C‐ (eGFRCys ). The prevalence of relative sarcopenia was higher than the prevalence of sarcopenia, especially in CKD stages 3b and 4 using eGFRCr ; these CKD stages were associated with the highest FMI. CKD stage was independently associated with low ALMI FMI for age using eGFRCys . BMI underestimated and %BF overestimated the prevalence of obesity compared with FMI. CKD was not independently associated with obesity by FMI. Conclusions: In CKD, conventional definitions of sarcopenia underestimate muscle deficits and %BF overestimates the prevalence of obesity. CKD is independently associated with relative sarcopenia, but not excess adiposity.